2017
DOI: 10.3390/ijerph14050522
|View full text |Cite
|
Sign up to set email alerts
|

Replication of High Fetal Alcohol Spectrum Disorders Prevalence Rates, Child Characteristics, and Maternal Risk Factors in a Second Sample of Rural Communities in South Africa

Abstract: Background: Prevalence and characteristics of fetal alcohol syndrome (FAS) and total fetal alcohol spectrum disorders (FASD) were studied in a second sample of three South African rural communities to assess change. Methods: Active case ascertainment focused on children with height, weight and/or head circumference ≤25th centile and randomly-selected children. Final diagnoses were based on dysmorphology, neurobehavioral scores, and maternal risk interviews. Results: Cardinal facial features, head circumference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 43 publications
4
57
1
Order By: Relevance
“…To the extent that these patterns of alcohol consumption directly translate to the incidence of FASD, previous studies in South Africa have also suggested that lower educational attainment and low socioeconomic status are associated with increased risk for FASD. In addition, these previous studies have found FASD to be associated with older maternal age, higher parity, lower body mass index, and tobacco use but not other drugs (May et al, ). U.S. survey data from the Behavioral Risk Factor Surveillance System 2015 to 2017 strongly correlated unmarried status with current drinking and binge drinking among pregnant women (Denny et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…To the extent that these patterns of alcohol consumption directly translate to the incidence of FASD, previous studies in South Africa have also suggested that lower educational attainment and low socioeconomic status are associated with increased risk for FASD. In addition, these previous studies have found FASD to be associated with older maternal age, higher parity, lower body mass index, and tobacco use but not other drugs (May et al, ). U.S. survey data from the Behavioral Risk Factor Surveillance System 2015 to 2017 strongly correlated unmarried status with current drinking and binge drinking among pregnant women (Denny et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…Fetal alcohol spectrum disorders (FASDs) comprise a range of effects resulting from prenatal alcohol exposure (PAE) including neurological abnormalities, cognitive and behavioral impairments, growth retardation, and craniofacial anomalies [1]. FASD affects 0.8% of the world's population, 2.0 to 5.0% of the European and North American populations [2,3], and 13.6 to 28% of high-risk rural populations in South Africa [4,5]. Despite being more common than autism spectrum disorder, which has a prevalence of 0.6% [6], FASD remains under-recognized [7].…”
Section: Introductionmentioning
confidence: 99%
“…We used the most recent data from the Fetal Alcohol Syndrome Epidemiologic Research (FASER) database (Hoyme et al, 2016;May et al, 2013b;May et al, 2017;May et al, 2018) to study the effects of alcohol on ocular measurements. This database comprises information compiled from a long-term epidemiological study of first grade students (ages 5 to 9 years) in five communities in South Africa.…”
Section: Methodsmentioning
confidence: 99%
“…Globally, the prevalence of FASD is estimated to be 7.7 per 1,000 children, and the prevalence of full FAS to be 1.5 per 1,000 children . In the United States, the prevalence of FASD is estimated to be 11.3 to 50.0 per 1,000 children (May et al, 2018), and the country with the highest prevalence of FASD is South Africa (Lange et al, 2017), which in recent general community studies has been found to be 23 to 28% among first grade children (May et al, 2016(May et al, , 2017. The annual cost of treatment for FASD in the United States was estimated at $6.5 billion in 2010 (Popova, Stade, Bekmuradov, Lange, & Rehm, 2011).…”
Section: Introductionmentioning
confidence: 99%